Stability challenges not addressed by harmonized guidance - AAPS workshop of the stability focus group, April 3rd- 4th, 2017 in Rockville, MD - Mohd M. Khan; Bowen Jiang; Anthony Mazzeo; Kim Huynh-Ba (SpringerOpen, 2018)
Abstract An American Association of Pharmaceutical Scientists (AAPS) workshop on stability challenges for clinical supplies and commercial distribution of drug product that are not addressed in the International Conference on Harmonization (ICH) Quality documents was held from April 3rd - 4th, 2017 in Rockville, MD. Seventeen subject matter experts (SME), from industry and the Food & Drug Administration (FDA) presented and facilitated the round-table discussions. A total of fifty-five participants that included experienced pharmaceutical scientists, both from small and large pharmaceutical companies and service providers, benefited from the opportunity to interact face-to-face with industry partners and regulatory agency SMEs. The two-day meeting was divided into five major sections to ensure face-to-face interactions and round-table discussions between participants and SMEs: 1) statistical approaches to stability, dissolution, and shelf life testing, 2) microbiological quality of drug products, 3) strategies to support distribution, unplanned excursions, and transportation of drug products, 4) regulatory considerations on stability testing of biologics, and 5) in-use stability during clinical and commercial phases. All in all, this interactive workshop focused on challenges and successes of addressing stability concerns that affect pharmaceutical development, manufacturing, distribution, and use of drug substances/products for which no or limited ICH guidance exists. The interactive meeting provided a unique opportunity to industrial scientists and regulatory agency liaisons to facilitate the discourse on how to address stability challenges that are not addressed in harmonized guidelines: this paper summarizes those discussions.